PROFESSIONAL TRAINING OF FUTURE PRESCHOOL TEACHERS IN THE FIELD OF CONTEXTUAL LEARNING TECHNOLOGIES - Xalilova, Mahfuza (Журнал иностранных языков и лингвистики, 2021)
The article deals with the development peculiarities of the subject artistic competence of future preschool teachers in the field of artistic and aesthetic education of children by means of contextual educational technologies. The students in question were being observed during the classes of Fundamentals of the Fine Arts with Methodology, the lessons of Decorative Arts with Methodology, as well as the Artistic Production and Design Fundamentals sessions. The purpose of the article is to reveal the methodology of contextual learning technologies’ implementation into the process of future preschool educators training and check their effectiveness in the realm of children’s artistic and aesthetic education experimentally.